2013
DOI: 10.1002/2013jb010231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fault heterogeneity on rupture dynamics: An experimental approach using ultrafast ultrasonic imaging

Abstract: [1] This study is devoted to the experimental investigation of the interaction of a propagating rupture with one or several mechanical heterogeneities. We developed a friction laboratory experiment where a soft elastic solid slides past a rigid flat plate. The system is coupled to an original medical imaging technique, ultrasound speckle interferometry, that allows observing the rupture dynamics as well as the emitted elastic shear wavefield into the solid body. We compare the dynamics of propagating rupture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Two loading configurations can be differentiated: shear, including direct shear, ring shear, and Couette shear (e.g. Brune, 1973;Archuleta and Brune, 1975;Schallamach, 1971;Latour et al, 2013b;Fig. 3a-c, e), and (biaxial) compression (e.g.…”
Section: Fault Block Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two loading configurations can be differentiated: shear, including direct shear, ring shear, and Couette shear (e.g. Brune, 1973;Archuleta and Brune, 1975;Schallamach, 1971;Latour et al, 2013b;Fig. 3a-c, e), and (biaxial) compression (e.g.…”
Section: Fault Block Modelsmentioning
confidence: 99%
“…The use of softer materials allows us to slow down the rupture process and make it more accessible by means of monitoring. This has been exploited by, e.g., Baumberger et al (2003), Yamaguchi et al (2011), andLatour et al (2013b) using gel sliders (Fig. 3e).…”
Section: Fault Block Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brörmann et al (2013) and Romero et al (2014) showed on interfaces with discrete contacts (pillars and spherical caps, respectively) that the transition from sticking to sliding is characterized by slip fronts propagating along the interface, similar to the observations of Rubinstein et al (2004) but at a two-dimensional interface. Latour et al (2013) studied experimentally the effect of interface barriers on frictional slip. They showed, using different configurations of barriers, that heterogeneities can cause rupture arrest/delay as well as increase/decrease of the rupture speed.…”
Section: Introductionmentioning
confidence: 99%
“…Two loading configurations can be differentiated: shear, including direct shear, ring shear, and Couette shear (e.g. Brune, 1973;Archuleta and Brune, 1975;Schallamach, 1971;Latour et al, 2013b;Fig. 3a-c, e), and (biaxial) compression (e.g.…”
Section: Fault Block Modelsmentioning
confidence: 99%